First Velarifictorus (Orthoptera: Gryllidae, Gryllinae) cricket described from Borneo (Southeast Asia) and notes on a co-occurring congener - Tan, Ming Kai; Ingrisch, Sigfrid; Wahab, Rodzay Bin Haji Abdul (Zootaxa, 2017)
Based on newly collected specimens from Brunei, a new species of Velarifictorus Randell, 1964 is described: Velarifictorus temburongensis sp. nov. This represents the first species of the genus Velarifictorus to be described from Borneo. Unexpectedly, the more widespread species Velarifictorus aspersus aspersus (Walker, 1869) was found together with the new species in the same locality, representing a new locality record for V. aspersus in Brunei. We used MaxEnt modelling to test if it was likely that this species occurs in Ulu Temburong and Borneo based on a set of bioclimatic predictors. While MaxEnt modelling showed that V. aspersus can occur in Borneo, it did not convincingly predict its occurrence in Ulu Temburong where it was found. Based on the model, maximum temperature of warmest month, minimum temperature of coldest month and annual precipitation are important bioclimatic variables to predict the distribution.